The centenary of Assemblies of God in South Africa: Historical reflections on theological education and ministry formation - Resane, Kelebogile T. (HTS teologiese studies, 2018)
The Assemblies of God (AOG) celebrates its centenary in 2017. The paper aims to show the historical development of theological education and ministerial training and formation in this denomination. It starts by showing how internationally AOG embraced the Bible Institute movement as a way of evangelism, church planting and growth from the early decades of the 20th century after the birth of the Pentecostal Movement. Then there is a South African scenario, lamenting the de-emphasis of the importance of theological education, though there was emphasis on evangelism and missional endeavours on the grassroots. The research unfolds the development of institutions from 1949 to the present. All in all, 10 institutions are identified and briefly explained, some of them with their demise. The article concludes by historical reflections on what was taught and identifies the gaps by suggesting that the Pentecostal curriculum should be relevant to the context of Africa by embracing inclusivity: Hidden Curriculum, Gender Studies, Inculturation and Liberation ideals and renaissance of pneumatology.